2022
DOI: 10.3389/fsurg.2022.916486
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Clinical Impacts of Post-Pancreatectomy Acute Pancreatitis After Pancreaticoduodenectomy: A Single-Center Retrospective Analysis of 298 Patients Based on the ISGPS Definition and Grading System

Abstract: BackgroundThe definition and grading system of post-pancreatectomy acute pancreatitis (PPAP) has recently been proposed by ISGPS. This study aimed to put this definition and classification into practice and investigate the potential risk factors and clinical impacts of PPAP.MethodsDemographic and perioperative data of consecutive patients who underwent pancreaticoduodenectomy (PD) from January 2019 to July 2021 were collected and analyzed retrospectively. The diagnostic criteria of PPAP published by ISGPS, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In our study, out of 78 patients with CR-PPAP, 77 were also diagnosed with CR-POPF. These results support the hypothesis of a possible physio-pathological connection between PPAP and POPF, although both complications may occur independently [26,27]. There is no clear explanation in the literature for the cause-and-effect mechanism between CR-PPAP and CR-POPF.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, out of 78 patients with CR-PPAP, 77 were also diagnosed with CR-POPF. These results support the hypothesis of a possible physio-pathological connection between PPAP and POPF, although both complications may occur independently [26,27]. There is no clear explanation in the literature for the cause-and-effect mechanism between CR-PPAP and CR-POPF.…”
Section: Discussionsupporting
confidence: 83%
“…Results of our multifactorial analysis in some of the included studies showed that being a woman as well as having a small pancreatic duct diameter, soft pancreatic texture, and high body mass index (BMI) were all risk factors of POAP after PD ( 14 , 16 , 17 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the diagnostic criteria, the high incidence of POAP deserves the attention of surgeons. In particular, the activation of pancreatic enzymes after POAP may lead to prolonged healing time or even non-healing of the pancreatic-intestinal anastomoses, resulting in postoperative pancreatic fistulas (POPFs), localized fluid accumulation in the abdominal cavity, infections, and even serious systemic complications ( 8 , 9 , 14 , 35 , 36 ). Some POAP may include acute necrotizing pancreatitis, which may pose serious hazards and even require secondary surgery for total pancreatectomy ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its freshness, only one study could be identified assessing the risk factors for ISGPS defined PPAP, identifying soft pancreatic texture and postoperative C-reactive protein over 180 mg/l as independent risk factors. 68 However, there is a growing body of evidence for factors associated with POAP. 9,69 POAP and POPF seem to share the majority of identified risk factors with pancreatic texture, high BMI, narrow duct, operative complexity, non-malignant histology, and male sex predisposing for POAP.…”
Section: Prediction Of Postoperative Pancreatitismentioning
confidence: 99%